Towards a consensus on dyslexia: findings from a Delphi study - Carroll, JM; Holden, C; Kirby, P; Thompson, PA; Snowling, MJ; Dyslexia Delphi Panel (Wiley, 2024)
Background: Dyslexia is one of the most common neurodevelopmental disorders. There have been many definitions over the past century and debate continues as to how dyslexia should be defined. This debate contributes to confusion and misinformation. We move beyond the debate by establishing areas of consensus among a wide range of experts. Methods: We conducted a Delphi study with a panel of dyslexia experts including academics, specialist teachers, educational psychologists, and individuals with dyslexia, asking them for their views on a set of key statements about dyslexia. We carried out two survey rounds, in each case accepting statements with greater than 80% consensus and reviewing and revising other statements using feedback from the expert panel. This was followed by discussion with a subset of the panel around a few statements with marginal consensus. Results: Forty-two statements were ultimately accepted. In the current paper we review those statements which pertain to a definition of dyslexia, demonstrate how they align to the research literature and build on previous definitions of dyslexia. Conclusions: There was considerable consensus in our expert panel that dyslexia is a difficulty in reading and spelling, associated with multiple factors, and that it frequently cooccurs with other developmental disorders. It was agreed that difficulties in reading fluency and spelling are key markers of dyslexia across different ages and languages. We conclude with a proposed new definition of dyslexia.